Pluripotency-State-Dependent Role of Dax1 in Embryonic Stem Cells Self-Renewal - Jianrong He; Yuda Cheng; Yan Ruan; Jiali Wang; Yanping Tian; Jiaqi Wang; Fengsheng Wang; Chen Zhang; Yixiao Xu; Lianlian Liu; Meng Yu; Jiangjun Wang; et al. (Stem Cells International)
Dax1(also known as Nr0b1) is regarded as an important component of the transcription factor network in mouse embryonic stem cells (ESCs). However, the role and the molecular mechanism of Dax1 in the maintenance of different pluripotency states are poorly understood. Here, we constructed a stable Dax1 knockout (KO) cell line using the CRISPR/Cas9 system to analyze the precise function of Dax1. We reported that 2i/LIF-ESCs had significantly lower Dax1 expression than LIF/serum-ESCs. Dax1KO ES cell lines could be established in 2i/LIF and their pluripotency was confirmed. In contrast, Dax1-null ESCs could not be continuously passaged in LIF/serum due to severe differentiation and apoptosis. In LIF/serum, the activities of the Core module and Myc module were significantly reduced, while the PRC2 module was activated after Dax1KO. The expression of most proapoptotic genes and lineage-commitment genes were drastically increased, while the downregulated expression of antiapoptotic genes and many pluripotency genes was observed. Our research on the pluripotent state-dependent role of Dax1 provides clues to understand the molecular regulation mechanism at different stages of early embryonic development.